Changing trends in mortality among solid organ transplant recipients hospitalized for COVID‐19 during the course of the pandemic. Issue 1 (7th October 2021) - Heldman, Madeleine R.; Kates, Olivia S.; Safa, Kassem; Kotton, Camille N.; Georgia, Sarah J.; Steinbrink, Julie M.; Alexander, Barbara D.; Hemmersbach‐Miller, Marion; Blumberg, Emily A.; Multani, Ashrit; Haydel, Brandy; La Hoz, Ricardo M.; et al.
Abstract : Mortality among patients hospitalized for COVID‐19 has declined over the course of the pandemic. Mortality trends specifically in solid organ transplant recipients (SOTR) are unknown. Using data from a multicenter registry of SOTR hospitalized for COVID‐19, we compared 28‐day mortality between early 2020 (March 1, 2020–June 19, 2020) and late 2020 (June 20, 2020–December 31, 2020). Multivariable logistic regression was used to assess comorbidity‐adjusted mortality. Time period of diagnosis was available for 1435/1616 (88.8%) SOTR and 971/1435 (67.7%) were hospitalized: 571/753 (75.8%) in early 2020 and 402/682 (58.9%) in late 2020 ( p < .001). Crude 28‐day mortality decreased between the early and late periods (112/571 [19.6%] vs. 55/402 [13.7%]) and remained lower in the late period even after adjusting for baseline comorbidities (aOR 0.67, 95% CI 0.46–0.98, p = .016). Between the early and late periods, the use of corticosteroids (≥6 mg dexamethasone/day) and remdesivir increased (62/571 [10.9%] vs. 243/402 [61.5%], p < .001 and 50/571 [8.8%] vs. 213/402 [52.2%], p < .001, respectively), and the use of hydroxychloroquine and IL‐6/IL‐6 receptor inhibitor decreased (329/571 [60.0%] vs. 4/492 [1.0%], p < .001 and 73/571 [12.8%] vs. 5/402 [1.2%], p < .001, respectively). Mortality among SOTR hospitalized for COVID‐19 declined between early and late 2020, consistent with trends reported in the general population. The mechanism(s) underlying improved survival require further study. Abstract : Data from the pre‐vaccine era show declining mortality among solid organ transplant recipients hospitalized for COVID‐19 over the course of the pandemic. Kalil comments on page 12 .